2022
DOI: 10.3390/su14159661
|View full text |Cite
|
Sign up to set email alerts
|

Research on Urban Community Elderly Care Facility Based on Quality of Life by SEM: Cases Study of Three Types of Communities in Shenzhen, China

Abstract: Aging in place has been proposed in response to increasing aging worldwide. Recently, many community elderly care facilities (CECFs) in China have been built to meet the desire of the elderly to age in place and help them live better in familiar environments. This study instituted a correlation evaluation system between the elderly’s quality of life (QOL) and their satisfaction with CECFs. It assessed the QOL of the elderly in urban communities in Shenzhen and identified the issues of CECFs that led to the eld… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…Some of the definitions of this concept are more general, such as "the level of what makes life good or high quality" [47] or that it is the "necessary preconditions for happiness" [48]; meanwhile, others are more specific: "a quality way of life is the desired outcome of policies and programs" [49]. Some authors define quality of life as an "indicator of the state of living and the well-being of people" [50]. Taking into consideration the lack of clarity surrounding the concept and the multidimensionality of the way in which it is discussed, certain authors consider it useless to look for a unique conceptualization [51,52].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some of the definitions of this concept are more general, such as "the level of what makes life good or high quality" [47] or that it is the "necessary preconditions for happiness" [48]; meanwhile, others are more specific: "a quality way of life is the desired outcome of policies and programs" [49]. Some authors define quality of life as an "indicator of the state of living and the well-being of people" [50]. Taking into consideration the lack of clarity surrounding the concept and the multidimensionality of the way in which it is discussed, certain authors consider it useless to look for a unique conceptualization [51,52].…”
Section: Literature Reviewmentioning
confidence: 99%
“…#6 cluster "community care" is a response to the call of aging in facilities. Many facilities have been built to help the elderly live better in familiar environments and realize their desire to age in place [36]. It was found that people have a strong demand for elderly care hotlines, establishing health records, on call nursing and doctor visits, medical lectures, regular physical examinations, and exercise and fitness [37].…”
Section: Research Hotspotsmentioning
confidence: 99%
“…Saha et al [10] similarly examined the antecedents of Indian elderly people's quality of life. Ma et al [8] also scrutinized the Chinese elderly, using quality of life as the dependent variable. Additionally, Sella et al [33] attested to the effect of sleeping in elderly individuals on quality of life.…”
Section: Quality Of Lifementioning
confidence: 99%
“…It can be inferred that such bountiful work indicates that quality of life is a valuable attribute to inspect. In general, numerous studies have employed quality of life as the dependent variable [7][8][9][10]. It can be inferred that quality of life is valuable to investigate as the dependent variable.…”
Section: Introductionmentioning
confidence: 99%